Impact of non-menthol flavours in tobacco products on perceptions and use among youth, young adults and adults: a systematic review. Issue 6 (21st November 2016) - Huang, Li-Ling; Baker, Hannah M; Meernik, Clare; Ranney, Leah M; Richardson, Amanda; Goldstein, Adam O
Abstract : Objective: This systematic review examines the impact of non-menthol flavours in tobacco products on tobacco use perceptions and behaviours among youth, young adults and adults. Data sources: English-language peer-reviewed publications indexed in 4 databases were searched through April 2016. Study selection: A search strategy was developed related to tobacco products and flavours. Of 1688 articles identified, we excluded articles that were not English-language, were not peer-reviewed, were qualitative, assessed menthol-flavoured tobacco products only and did not contain original data on outcomes that assessed the impact of flavours in tobacco products on perceptions and use behaviour. Data extraction: Outcome measures were identified and tabulated. 2 researchers extracted the data independently and used a validated quality assessment tool to assess study quality. Data synthesis: 40 studies met the inclusion criteria. Data showed that tobacco product packaging with flavour descriptors tended to be rated as more appealing and as less harmful by tobacco users and non-users. Many tobacco product users, especially adolescents, reported experimenting, initiating and continuing to use flavoured products because of the taste and variety of the flavours. Users of many flavoured tobacco products also showed decreased likelihood of intentions to quit compared with non-flavoured tobacco product users. Conclusions: Flavours in most tobacco products appear to play a key role in how users and non-users, especially youth, perceive, initiate, progress and continue using tobacco products. Banning non-menthol flavours from tobacco products may ultimately protect public health by reducing tobacco use, particularly among youth.